Differentiated instruction - Gregory, Gayle (Best of Corwin series., 2011)
The definitive guide to differentiated instruction The Best of Corwin:Differentiated Instruction features a tapestry of critical information to guide teachers in implementing differentiation. Helpful tools include standards-based lesson- and unit- planning templates, graphic organizers, and brain-based research. The compilation also provides: Strategies for understanding students' needs Tips for accommodating various learning styles Curriculum approaches for data-driven instruction Proven best teaching practices Guidance in creating a positive learning environment Also includ.